Práticas pedagógicas colaborativas: uma experiência de círculos de cultura entre a coordenação e professores da EJA - Queiroz, Flávia Mariana da Silva (2018)
The present research-intervention had as an object an experience with Círculo de Cultura, having as subjects of research polyvalent and licensed teachers that work in the Education of Young and Adults (EJA) at the Escola de Prefeitura de Guarulhos "EPG Hamilton Félix de Souza" in the region metropolitan of São Paulo. The reflective meetings with the researcher, who was also a pedagogical coordinator in the modality under study, were recorded and later analyzed some reflections that allowed the demonstration of the potentiality of the Culture Circles encouraged by the researcher as research methodology in teacher training, a space of questions without answers with a perspective of action-reflection-action, raising the possibility of implementing the Pedagogical Political Project (PPP) of the school studied and the Table of Knowledge, a curricular reference of the municipality. This work also demonstrated the importance of collaboration in the construction of groups and the teaching itself in its autonomy for the development of possible shared practices that walk to the student, from schooling in the EJA, transform their consciousness and life trajectory. This research demonstrated that the Círculo de Cultura methodology promotes participation and the exchange of experience, in an emancipatory reflection that increases the autonomy and collaboration, which reverberates in an educative act surpassing the naive conscience.